KOMITMEN ORGANISASI PADA KARYAWAN DI MIRACLE AESTHETIC CLINIC DI SURABAYA - Rahayu, Wulan (Universitas Ahmad Dahlan, 2014)
ABSTRACTThe research is to study the reason why the worker commits to the company organization and to study the factors influencing organization commitment to the workers of Miracle Aesthetic Clinic. This research is done in area M.H THAMRIN Street No. 40, Dr. Sutomo District, Tegal Sari, Surabaya. The subjects of this study are the workers of Miracle Aesthetic Clinic who have worked here for a long time. The method of this research is qualitative using strategy of inquiry phenomenology, which is oriented to study the phenomena happened by studying the subject perseption. The data is collected by interviewing the close mate of the subject as triangulation. The researcher used theme analysis to analyze the data. The result of this study, which is done in one of beauty clinic in Surabaya, showed that the respondents have high commitment and still choose to stay at Miracle Aesthetic Clinic, because Miracle always give the best things to its workers. Some factors influencing the good commitment of workers, as suitable with Minner theory, is harmonic relationship between workers and with their board, their dreams when joining the Miracle Aesthetic Clinic, and their experiences felt since first joining and during working time. Besides that, the researcher found new factors unmatched with the theory, which were the high support from family and their proud to join the Miracle Aesthetic Clinic.Keyword: Commitment Organization